Partial replacement effect of montmorillonite with cellulose nanowhiskers on polylactic acid nanocomposites - Arjmandi, Reza (Elsevier, 2015)
In this study, hybrid montmorillonite/cellulose nanowhiskers (MMT/CNW) reinforced polylactic acid (PLA) nanocomposites were produced through solution casting. The CNW filler was first isolated from microcrystalline cellulose by chemical swelling technique. The partial replacement of MMT with CNW in order to produce PLA/MMT/CNW hybrid nanocomposites was performed at 5 parts per hundred parts of polymer (phr) fillers content, based on highest tensile strength values as reported in our previous study. MMT were partially replaced with various amounts of CNW (1, 2, 3, 4 and 5. phr). The tensile, thermal, morphological and biodegradability properties of PLA hybrid nanocomposites were investigated. The highest tensile strength of hybrid nanocomposites was obtained with the combination of 4. phr MMT and 1. phr CNW. Interestingly, the ductility of hybrid nanocomposites increased significantly by 79% at this formulation. The Young's modulus increased linearly with increasing CNW content. Thermogravimetric analysis illustrated that the partial replacement of MMT with CNW filler enhanced the thermal stability of the PLA. This is due to the relatively good dispersion of fillers in the hybrid nanocomposites samples as revealed by transmission electron microscopy. Interestingly, partial replacements of MMT with CNW improved the biodegradability of hybrid nanocomposites compared to PLA/MMT and neat PLA.